The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.2478/acro-2013-0003
|View full text |Cite
|
Sign up to set email alerts
|

Population of Tengmalm’s Owl Aegolius Funereus in Kopaonik National Park (Central Serbia)

Abstract: The altitudinal distribution, breeding density and population size of Tengmalm’s Owl Aegolius funereus was studied in Kopaonik National Park (central Serbia) during the 2011 and 2012 breeding seasons. The size of the study area was 24 km2. The survey method applied was a line transect in combination with stop points and playback of territorial male call. During the two-year research project, 37 territories were located. In Kopaonik National Park, Tengmalm’s Owl males inhabit Norway Spruce Picea abies, mixed No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
(10 reference statements)
1
8
0
Order By: Relevance
“…Across the European distribution range, both species are highly dependent on old growth (>80 years old), and primarily, coniferous forest stands, choosing dry and dead trees with cavities for breeding and food storage [ 45 ]. In Southern Europe, particularly on the Balkan Peninsula, both species prefer higher elevations, north-faced slopes, and medium-to-dense forests with a cold and humid climate [ 46 , 47 , 48 ]. Therefore, it can be assumed that Boreal and Eurasian Pygmy Owls are stenovalent habitat specialists with a narrow tolerance range and few possibilities of adaptation, which can only survive in the specific, above-mentioned environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Across the European distribution range, both species are highly dependent on old growth (>80 years old), and primarily, coniferous forest stands, choosing dry and dead trees with cavities for breeding and food storage [ 45 ]. In Southern Europe, particularly on the Balkan Peninsula, both species prefer higher elevations, north-faced slopes, and medium-to-dense forests with a cold and humid climate [ 46 , 47 , 48 ]. Therefore, it can be assumed that Boreal and Eurasian Pygmy Owls are stenovalent habitat specialists with a narrow tolerance range and few possibilities of adaptation, which can only survive in the specific, above-mentioned environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…About 75% of the study area consists of high-mountain forests (mostly Norway spruce, Picea abies), 22% of open grassland-rocky terrain, and 3% of built-up areas. A detailed description of the study area can be found in earlier publications (Rajković et al, 2010(Rajković et al, , 2013.…”
mentioning
confidence: 99%
“…Average population density of the species in the Pirin NP was calculated at 9.6 territories/1000 ha of appropriate habitat which is comparatively high value. For comparison the same value at Kopaonik Mt., Central Serbia is 7.7 (Rajkovic et al 2013), at Krim Mt., Central Slovenia 2.8 (Vrezec 2003), in France 6-13 (Jonieniaux & Durand 1987), in W-Finland 0.1-2.6 (Korpimäki & Norrdahl 1989), in Sweden up to 4.8 in peak years (Kallander 1964).…”
Section: Population Numbers Trends Changes In the Distributionmentioning
confidence: 89%
“…Kopaonik, Central Serbia, and a density of 7.7 territories/1000 ha was reported. The species was found mostly in Norway Spruce forests (Rajkovic et al 2013). The distribution, biology and habitat requirements of the Pygmy Owl were studied in parts of Romanian Carpathians, where the population density was calculated at 6.1-7.3 pairs/1000 ha (Mestecaneanu & Mestecaneanu 2019).…”
Section: Introductionmentioning
confidence: 99%